Determination of heat stress and calcium chloride application in loquat storage - Tzortzakis, Nikos G.; Sergentani, C. (My University, 2015)
The effects of heat stress (HS) and/or calcium chloride (CaCl2) on loquat (Eriobotrya japonica Lindl. 'Trouloti') fruit quality and storability were investigated in atmospheric air (AA - continuous air open flow system). Loquats were dipped in a water bath (at 45°C for 10 min, HS) and/or in CaCl2 (2% w/v for 10 min) and then stored under AA conditions at 5.5°C for 0, 15 and 30 days. A batch of fruits was removed after 0, 15, and 30 days to AA and stored for an additional 5 days at room temperature (RT). Loquat firmness was maintained in fruits treated with HS+CaCl2 after 5 days at RT and this was evident (including CaCl2 application) in fruits stored up to 30 days at 5.5°C. Similarly, under AA conditions, HS+CaCl2 and CaCl2 increased fruit sweetness and reduced acidity. The HS+CaCl2 increased (up to 50%) the respiration rate at 15 days of storage. On the other hand, total phenols decreased in fruits treated with HS+CaCl2 and stored up to 30 days at 5.5°C, while fruits stored at RT did not change. The number of fruits with brownish discoloration decreased (up to 39%, compared to controls) in fruits treated with HS+CaCl2 or CaCl2 (averaging only 10% of total fruit). HS alone accelerated browning and fruit decay development. Fruits stored for 5 days at RT following exposure to HS and/or CaCl2 increased respiration rate, sweetness and browning. No major differences were observed in fruit dry matter content and water loss. Following sensory evaluation, all panelists identified differences among treatments, with the HS+CaCl2 treatment giving the best preference (90%), maintaining loquat appearance and sweetness and no detected differences in fruit aroma and texture. Thus, the HS+CaCl2 on loquat maintained fruit quality, as indicated by panelists' preference.
Keywords: Calcium; Eriobotrya japonica; Postharvest; Sensory evaluation